Immunotherapy strategies for EGFR-mutated advanced NSCLC after EGFR tyrosine-kinase inhibitors failure - Li, Xingyuan; Huang, Huayan; Sun, Yingjia; Jiang, Qing; Yu, Yongfeng (Frontiers in Oncology, 2023)
Background This study aimed to investigate the efficacy of immunotherapy, as monotherapy or in combination, comparing to chemotherapy with or without anti-angiogenesis for advanced non-small cell lung cancer (NSCLC) patients progressing to epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs). Methods We retrospectively analyzed patients with advanced NSCLC harboring EGFR mutations who received immune checkpoint inhibitors (ICI) and/or chemotherapy after EGFR-TKIs failure at Shanghai Chest Hospital between Aug 2016 and Oct 2022. According to the subsequent immunotherapy regimen, the patients were assigned to ICI monotherapy (IM), IO plus anti-angiogenesis (IA), ICI plus chemotherapy (IC), ICI plus chemotherapy plus anti-angiogenesis (ICA). Eligible patients undergoing standard chemotherapy were assigned to chemotherapy plus anti-angiogenesis (CA) and chemotherapy alone (CM). Efficacy was evaluated according to the RECIST 1.1version, and calculated the objective response rate (ORR) and disease control rate (DCR). Survival curves were plotted using the Kaplan-Meier method, and the median progression-free survival (PFS) was calculated. Differences among survival curves of the six groups were assessed using the log-rank test. Results A total of 237 advanced NSCLC patients with EGFR mutations were included in this study. Of the 160 patients who received immunotherapy, 57 received ICI monotherapy, 27 received ICI plus anti-angiogenesis therapy, 43 received ICI plus chemotherapy, and 33 received ICI plus anti-angiogenesis plus chemotherapy. 77 patients received standard chemotherapy, of which 30 received chemotherapy plus anti-angiogenesis and 47 received chemotherapy alone. Patients in ICA group showed significant longer PFS than IM (7.2 vs 1.9 months, P=0.011), IA (7.2 vs 4.8 months, P=0.009) and CM group (7.2 vs 4.4 months, P=0.005). There was no significant difference in PFS between the ICA and IC (7.2 vs 5.6 months, P=0.104) or CA (7.2 vs 6.7 months, P=0.959) group. Meanwhile, the ICA group showed the highest ORR and DCR (36.4% and 90.9%) compared to the other five groups. The IC group had a higher ORR than the IA and CA group (32.6% vs 7.4% vs 10.0%, respectively), but the DCR was comparable (79.1% vs 74.1% vs 76.7%, respectively). The ORR of the CM group was 6.4% and the DCR was 66.0%. IM group showed the lowest ORR and DCR (1.8% and 36.8%). Treatment-related adverse events (TRAEs) of grade 3 or worse occurred in 9 (27.3%) patients in the ICA group, 6 (20.0%) in the CA group, 7 (14.9%) in the CM group, 5 (11.6%) in the IC group, 5 (8.8%) in the IM group, and 2 (7.4%) in the IA group. Conclusion NSCLC patients with positive EGFR mutations after EGFR-TKIs failure received subsequent immunotherapy plus anti-angiogenesis and chemotherapy are likely to have more benefits in ORR, DCR and mPFS.